Geochemical evolution in defunct gold mine tailings and modelling of seepage water quality: an investigation of a typical tailings storage facility in the East Rand, Johannesburg, South Africa - Fourie, Petrus Johannes (University of the Free State, 2022)
The geochemical evolution in a defunct tailings dam was investigated in the East Rand Basin of the Witwatersrand. The research aimed to geochemically characterise the tailings, quantify oxygen infiltration into the tailings dam and develop a numerical geochemical model to simulate the geochemical evolution within the dam over the past 60 years. Two holes (3.4 and 6 m deep, respectively) were hand-augured into the tailings dam to geochemically characterize the tailings. Tailings samples were collected at roughly 15 cm intervals. On selected samples from the 6 m hole, the whole-rock elemental composition (using X-ray Fluorescence and a Leco Element Analyser) was performed, as well as acid-base testing, X-ray diffraction and Scanning Electron Microscope. Field measurements of pH, Electrical Conductivity (EC) and Oxidation-reduction Potential (ORP) were performed on drilled-out samples of the 3.4 m hole. The oxygen concentration in the tailings gas phase was measured to correlate the oxygen ingress with the other measured geochemical parameters and for later use in the geochemical model. Air chambers were installed in the 6 m hand-augered hole. Each air chamber comprised a perforated 7 cm high plastic container wrapped in a geotextile that is then connected with an 8 mm silicon pipe. Air collection chambers were installed at depths of 0.5 m, 1 m, 1.5 m, 2 m, 2.5 m, 3 m, 4 m, 5 m, and 6 m. Based on the oxygen concentration in the gas phase, the top of the tailings dam was subdivided into three geochemical environments, namely the Oxic Zone (0-2 m), the Transition Zone (2-4 m), and the Anoxic Zone (>4 m). The data shows that oxygen penetrates slightly deeper during the winter than in the summer months. The seasonal effect could be attributed to the higher rainfall in the summer than in winter. A conceptual model of the geochemical evolution within the tailings dam was developed. The aim was to outline the major mechanisms that influence the geochemical evolution in the dam to include them in the numerical model. Batch reactor testing was performed at three different pH's (pH ~3, pH ~5 and pH ~7) to back-calculate the effective surface area of the pyrite in a tailings sample based upon its reaction during the experiment. The experiments were performed over about 14 days. Except for the last few days, samples were collected twice a day. The sulphate production was the lowest in the pH ~3 experiment and the highest in the pH ~7 experiment. This is because pyrite oxidation by oxygen is inversely proportional to hydrogen activity. The modelled pyrite reaction rate fitted the results for all three experiments. The optimal surface area was determined at 1046.26 g/cm². A numerical geochemical model was performed to simulate the geochemical evolution within the dam over the past 60 years. The primary objective of the modelling was to improve the understanding of the mechanisms that control the geochemical reactions and dispersion of chemicals. A secondary objective of the model was to match the model results with the observations 60 years after closure.
Thesis (Ph.D. (Geology))--University of the Free State, 2022